2009
DOI: 10.1124/mol.109.054783
|View full text |Cite
|
Sign up to set email alerts
|

Five Amino Acids in the Innermost Cavity of the Substrate Binding Cleft of Organic Cation Transporter 1 Interact with Extracellular and Intracellular Corticosterone

Abstract: We have shown previously that Leu447 and Gln448 in the transmembrane helix (TMH) 10 of rat organic cation transporter rOCT1 are critical for inhibition of cation uptake by corticosterone. Here, we tested whether the affinity of corticosterone is different when applied from the extracellular or intracellular side. The affinity of corticosterone was determined by measuring the inhibition of currents induced by tetraethylammonium ϩ (TEA ϩ ) in Xenopus laevis oocytes expressing rOCT1. Either corticosterone and TEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 24 publications
2
65
1
2
Order By: Relevance
“…Assuming monomeric function of rOct1, well supported hypotheses concerning substrate binding and translocation have been raised. Neglecting allosteric effects of substrate binding to different monomers, differential effects of single point mutations on different substrates were interpreted to indicate that the substrate binding region of rOct1 contains overlapping binding domains for different substrates (10,37). Although our present data do not exclude subtle allosteric effects between monomers, they show that allosteric interaction between monomers does not have main functional importance.…”
Section: Discussioncontrasting
confidence: 38%
“…Assuming monomeric function of rOct1, well supported hypotheses concerning substrate binding and translocation have been raised. Neglecting allosteric effects of substrate binding to different monomers, differential effects of single point mutations on different substrates were interpreted to indicate that the substrate binding region of rOct1 contains overlapping binding domains for different substrates (10,37). Although our present data do not exclude subtle allosteric effects between monomers, they show that allosteric interaction between monomers does not have main functional importance.…”
Section: Discussioncontrasting
confidence: 38%
“…Moreover, X-ray crystal structures of P-gp (Aller et al, 2009) and the multidrug-binding transcription regulator QacR (Schumacher and Brennan, 2003) reveal the presence of multisite binding pockets. With respect to the OCTs, a number of studies have suggested that inhibitors of OCT transport display allosteric interactions at multiple sites (e.g., Volk et al, 2003Volk et al, , 2009Popp et al, 2005;Lee et al, 2009;Minuesa et al, 2009;Egenberger et al, 2012). Furthermore, the results of site-directed studies of OCT function consistently suggest that substrates must interact with spatially distinct sites within the large hydrophilic translocation pathway suspected to exist with OCT1 (Popp et al, 2005) and OCT2 (Zhang et al, 2005;Pelis et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…21 Because ASP + was used as a probe substrate, we first docked ASP + into two predicted binding sites and selected the site with the best score (−6.08) for all subsequent docking. Next, we validated the accuracy of the comparative model of the OCT1 transporter by confirming that (1) known OCT1 substrates docked favorably against the predicted binding site and (2) residues implicated in OCT1 transport 12,14,16,17 were localized in the predicted binding site, as follows. First, we docked 15 known OCT1 endogenous and drug substrates against the predicted binding site ( Figure 1A).…”
Section: ■ Resultsmentioning
confidence: 99%
“…The equivalent residues in rat have also been implicated in ligand−transporter interactions. 17 Prediction of New Ligands by Virtual Screening and Validation by HTS. We predicted new ligands of OCT1 by docking each one of the 1780 compounds in the Pharmakon drug library (MicroSource Discovery Systems; http://www.…”
Section: ■ Resultsmentioning
confidence: 99%